2018
DOI: 10.1007/s10680-018-9478-0
|View full text |Cite
|
Sign up to set email alerts
|

Residential Segregation of European and Non-European Migrants in Sweden: 1990–2012

Abstract: In this paper, we analyse how a migrant population that is both expanding and changing in composition has affected the composition of Swedish neighbourhoods at different scales. The analysis is based on Swedish geocoded individual-level register data for the years 1990, 1997, 2005, and 2012. This allows us to compute and analyse the demographic composition of neighbourhoods that range in size from encompassing the nearest 100 individuals to the nearest 409,600 individuals. First, the results confirm earlier fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…The Index of Dissimilarity was chosen because of its simplicity and because the grid data offer already a standardisation according to the territorial sub-division. Moreover this index has been used in several studies on residential segregation (see for example Friedman 2008;Iceland et al 2013Iceland et al , 2014Logan and Parman 2017;Malmberg et al 2018). This part intends to answer research questions 1, 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…The Index of Dissimilarity was chosen because of its simplicity and because the grid data offer already a standardisation according to the territorial sub-division. Moreover this index has been used in several studies on residential segregation (see for example Friedman 2008;Iceland et al 2013Iceland et al , 2014Logan and Parman 2017;Malmberg et al 2018). This part intends to answer research questions 1, 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…Since the turn of the 21st century, an unprecedented number of people (1.6 million) have immigrated to Sweden, with a large proportion consisting of refugees and their families (Statistics Sweden, ). Although the country is renowned for its extensive welfare system and its support for integration programmes, the migrant population experiences high levels of residential segregation (Malmberg, Nielsen, Andersson, & Haandrikman, ). Since the 1970s, migrants have been concentrated in certain residential areas in the urban periphery (Hedberg, ).…”
Section: Swedish Contextmentioning
confidence: 99%
“…Although the country is renowned for its extensive welfare system and its support for integration programmes, the migrant population experiences high levels of residential segregation (Malmberg, Nielsen, Andersson, & Haandrikman, 2016). Since the 1970s, migrants have been concentrated in certain residential areas in the urban periphery (Hedberg, 2009).…”
Section: Swedish Contextmentioning
confidence: 99%
“…Levels of residential segregation have been consistently high in Sweden during the last decades. Studies have found that income-based segregation has increased, while ethnic segregation has remained stable or even slightly decreased (Amcoff et al, 2014;Andersson & K€ ahrik, 2016;Andersson & Turner, 2014;Andersson et al, 2018;Malmberg et al, 2018;Niedomsyl et al, 2015;Nielsen & Hennerdal, 2017). Although ethnic and socioeconomic segregation cannot be equated, they tend to correspond, as socioeconomically deprived areas are also likely to have a high concentration of foreign-born individuals (Biterman, 2010).…”
Section: Introductionmentioning
confidence: 99%